Brain Microvascular Pericytes in Vascular Cognitive Impairment and Dementia - Uemura, Maiko T.; Maki, Takakuni; Ihara, Masafumi; Lee, Virginia M. Y.; Trojanowski, John Q. (Frontiers in Aging Neuroscience, 2020)
Pericytes are unique, multi-functional mural cells localized at the abluminal side of the perivascular space in microvessels. Originally discovered in nineteenth century, pericytes had drawn less attention until decades ago mainly due to lack of specific markers. Recently, however, a growing body of evidence has revealed that pericytes play various important roles: development and maintenance of blood-brain barrier (BBB), regulation of the neurovascular system (e.g., vascular stability, vessel formation, cerebral blood flow, etc.), trafficking of inflammatory cells, clearance of toxic waste products from the brain, and acquisition of stem cell-like properties. In the neurovascular unit, pericytes perform these functions through coordinated crosstalk with neighboring cells including endothelial, glial, and neuronal cells. Dysfunction of pericytes contribute to a wide variety of diseases that lead to cognitive impairments such as cerebral small vessel disease (SVD), acute stroke, Alzheimer’s disease (AD), and other neurological disorders. For instance, in SVDs, pericyte degeneration leads to microvessel instability and demyelination while in stroke, pericyte constriction after ischemia causes a no-reflow phenomenon in brain capillaries. In AD, which shares some common risk factors with vascular dementia, reduction in pericyte coverage and subsequent microvascular impairments are observed in association with white matter attenuation and contribute to impaired cognition. Pericyte loss causes BBB-breakdown, which stagnates amyloid β clearance and the leakage of neurotoxic molecules into the brain parenchyma. In this review, we first summarize the characteristics of brain microvessel pericytes, and their roles in the central nervous system. Then, we focus on how dysfunctional pericytes contribute to the pathogenesis of vascular cognitive impairment including cerebral ‘small vessel’ and ‘large vessel’ diseases, as well as AD. Finally, we discuss therapeutic implications for these disorders by targeting pericytes.